Multimorbidity and quality of primary care after release from prison: a prospective data-linkage cohort study - Lucas Calais-Ferreira; Amanda Butler; Stephan Dent; David B. Preen; Jesse T. Young; Stuart A. Kinner (BMC, 2022)
Abstract Background The period after release from prison can be challenging, especially due to a higher risk of morbidity and mortality despite commonly increased use of healthcare services. However, little is known about the quality of the healthcare offered to this population, which limits the possibility of addressing this important health inequity. This study characterised multimorbidity and investigated the relationship between multimorbidity and quality of primary healthcare in adults within 2 years after release from prison. Methods This was a prospective cohort study of 1046 participants of a service brokerage intervention after release from prison between August 2008 and July 2010 in Queensland, Australia. Participants had their baseline survey and clinical data linked prospectively with their medical, correctional and death records. Multimorbidity was ascertained using the Cumulative Illness Rating Scale and classified into three categories: none, moderate (morbidity in 2-3 domains) and complex (morbidity in 4 or more domains). Outcomes were Usual Provider Continuity Index (UPCI), Continuity of Care (COC) Index, and having at least one extended primary care consultation (> 20 minutes). Descriptive statistics and logistic regression were used in the analyses. Results Multimorbidity was present for 761 (73%) participants, being more prevalent among females (85%) than males (69%), p < 0.001. Moderate multimorbidity was not associated with UPCI or COC, but was associated with having at least one long consultation (AOR = 1.64; 95% CI:1.14-2.39), after adjusting for covariates. Complex multimorbidity was positively associated with all outcomes in the adjusted models. Indigenous status was negatively associated with UPCI (AOR = 0.54; 95% CI: 0.37-0.80) and COC (AOR = 0.53; 95% CI: 0.36-0.77), and people younger than 25 years were at 36% lower odds (AOR = 0.64; 95% CI: 0.44-0.93) of having a long consultation than the middle-aged group (25-44 years) in the adjusted models. Conclusion Moderate multimorbidity was associated with having at least one extended primary care consultation, but not with adequate continuity of care, for adults within 2 years of being released from prison. Nearly half of those with complex multimorbidity did not receive adequate continuity of care. The quality of primary care is inadequate for a large proportion of adults released from prison, constituting an important and actionable health inequity.